i am stuck on the following problem. here is a pic of the problem

http://imgur.com/GIU9ux3

f(x) = 5x-4

a = 3

f(a) = 5(3) - 4 = 15-4 = 11

f(x) - f(a) = 5x - 4 - 11 = 5x - 15 = 5(x-3)

[f(x) - f(a)]/(x-a) = (5x - 15)/(x-3) = [5(x-3)] / (x-3)

The x-3 terms cancel, and you're left with

[f(x) - f(a)]/(x-a) = 5

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up